Educational research and policy, how do they relate? - Husen, Torsten, 1916-2009; Kogan, Maurice (Pergamon Press, 1984)
Educational Research and Policy: How do They Relate? contains the proceedings of a four-day symposium held at Wijk, Lidingo-Stockholm in June 1982.